Analysis of the Effectiveness of Income Tax Policy on Trade Transactions via Electronic Systems (E-Commerce) in Efforts to Increase Tax Revenue in 2018-2020 (Case Study at KPP Pratama Jakarta Jatinegara) - Maidah, Ridwan Abdul Hakam; Hardan, Ahmad Omar (Indonesian Scientific Publication, 2023)
According to the Association of Indonesian Internet Service Providers (APJII) in 2019-2020 internet users in Indonesia were 196.71 million people out of a total population of 266.91 million or 73.7% of the total. Along with the soaring use of the internet in Indonesia, this has created an opportunity for many people to do business through the internet (e commerce). This study aims to analyze the effectiveness of income tax policies on trade transactions through electronic systems (e-commerce), along with the inhibiting and driving factors in increasing tax revenues. The author uses the theory of Martani and Lubis (2009:55) quoted in the journal Journal of Governance vol.1. no. 2. 2021. This study uses a qualitative approach with a descriptive method. The data collection techniques used are interview, observation, and documentation methods. From the results of this study, the increase in income tax revenue on trade through electronic systems (e-commerce) cannot be said to be effective. In the realization of e-commerce tax revenue has not been realized optimally. Because not everyone understands the tax on e-commerce transactions and there is no stipulation of a mechanism from several merchants to register, this makes the data not optimally detected. This happens because the data for online business actors is incomplete, the lack of socialization provided, lack of awareness, lack of legal clarity, and efforts that can be made are to be able to carry out socialization on an ongoing basis through online and offline, collaborate with relevant stakeholders in encouraging taxpayers make a TIN, and build awareness in the scope of taxes on e-commerce transaction.